Development of a Poppet-Type Pneumatic Servo Valve - Takahiro Kanno (Applied Sciences, 2018)
In pneumatic positioning and force-control systems, spool-type servo valves are widely used for obtaining quick responses and precise control. However, air leakage from these valves results in increased energy consumption. To address this problem, we developed a three-port poppet-type servo valve to reduce air leakage. The developed valve consists of a camshaft, two orifices, two metal balls, and a housing with two flow channels. The metal ball is pushed by fluid, and spring force closes the orifice. The port opens when the cam rotates and pushes the ball. The cam shape and orifice size were designed to provide the desired flow rate. The specifications of the DC motor for rotating the camshaft were determined considering the fluid force on the ball. Static and dynamic characteristics of the valve were measured. We experimentally confirmed that air leakage was 0.1 L/min or less. The ratio of air leakage to maximum flow rate was only 0.37%. Dynamic characteristic measurements showed that the valve had a bandwidth of 30 Hz. The effectiveness of the valve was demonstrated through experiments involving pressure and position control.